2011
DOI: 10.1186/1471-244x-11-2
|View full text |Cite
|
Sign up to set email alerts
|

Markers of thrombogenesis are activated in unmedicated patients with acute psychosis: a matched case control study

Abstract: BackgroundAntipsychotic treatment has been repeatedly found to be associated with an increased risk for venous thromboembolism in schizophrenia. The extent to which the propensity for venous thromboembolism is linked to antipsychotic medication alone or psychosis itself is unclear. The objective of this study was to determine whether markers of thrombogenesis are increased in psychotic patients who have not yet been treated with antipsychotic medication.MethodsWe investigated the plasma levels of markers indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 39 publications
10
28
0
Order By: Relevance
“…The mentioned study 15 confirms the presence of higher markers of thrombogenesis in plasma of acute psychotic patients compared to healthy persons (D-dimer, factor VIII as well as soluble P-selectin).…”
Section: Discussionsupporting
confidence: 86%
“…The mentioned study 15 confirms the presence of higher markers of thrombogenesis in plasma of acute psychotic patients compared to healthy persons (D-dimer, factor VIII as well as soluble P-selectin).…”
Section: Discussionsupporting
confidence: 86%
“…Disturbances in blood coagulability, potentially contributing to the increased incidence of cardiovascular disease among patients with schizophrenia, have not only been associated with anti-psychotic medication use but have also been reported in medication-naive patients with psychosis. 54 …”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing unmedicated, acutely unwell cases of schizophrenia defined by DSM-IV or ICD-10 criteria with healthy controls have reported increased soluble P (sP)-selectin, sL-selectin, D-dimer levels in serum as well as increased number of integrin α IIb β IIIa receptors on platelets in schizophrenia (Iwata et al 2007; Masopust et al 2011; Walsh et al 2002). These findings could not be explained by concurrent inflammation or physical illness (Masopust et al 2011). One study focusing on different selectin molecules found that serum sL-selectin was increased in schizophrenia even after controlling for lymphocyte count (Iwata et al 2007).…”
Section: Schizophrenia Is Associated With Alteration In Components Ofmentioning
confidence: 99%